A novel emergency department based prevention intervention program for people living with HIV: evaluation of early experiences - Trott Alexander T; Lindsell Christopher J; Raab Dana L; Lyons Michael S; Fichtenbaum Carl J (BMC, 2007)
Abstract Background HIV prevention is increasingly focused on people living with HIV (PLWH) and the role of healthcare settings in prevention. Emergency Departments (EDs) frequently care for PLWH, but do not typically endorse a prevention mission. We conducted a pilot exploratory evaluation of the first reported ED program to address the prevention needs of PLWH. Methods This retrospective observational cohort evaluation reviewed program records to describe the first six months of participants and programmatic operation. Trained counselors provided a risk assessment and counseling intervention combined with three linkage interventions: i) linkage to health care, ii) linkage to case management, and iii) linkage to partner counseling and referral. Results Of 81 self-identified PLWH who were approached, 55 initially agreed to participate. Of those completing risk assessment, 17/53 (32%, 95 CI 20% to 46%) reported unprotected anal/vaginal intercourse or needle sharing in the past six months with a partner presumed to be HIV negative. Counseling was provided to 52/53 (98%). For those requesting services, 11/15 (73%) were linked to healthcare, 4/23 (17%) were coordinated with case management, and 1/4 (25%) completed partner counseling and referral. Conclusion Given base resources of trained counselors, it was feasible to implement a program to address the prevention needs for persons living with HIV in an urban ED. ED patients with HIV often have unmet needs which might be addressed by improved linkage with existing community resources. Healthcare and prevention barriers for PLWH may be attenuated if EDs were to incorporate CDC recommended prevention measures for healthcare providers.